MEANS OF EXPRESSING MATERIAL CATEGORIES IN DIFFERENT LANGUAGES - Shukhratova Mukhlisaxon Shukhratjon kizi (Web of Journals Publishing, 2025)
This article examines the linguistic nature of the category of modality in different languages, its scope of content and means of expression. Modality is an important grammatical-semantic category that indicates the speaker's attitude to reality, and is manifested in each language through its own means. The article examines the grammatical, lexical and syntactic forms of modality in English, Russian and Uzbek based on a comparative analysis. Also, the epistemic, deontic and pragmatic manifestations of modality are explained with examples.
Keywords: Modality, category of modality, modal verbs, epistemic modality, deontic modality, lexical modality, grammatical means, syntactic means, pragmatics, linguistics.